STOCK: Structure mapper and online coarse‐graining kit for molecular simulations. Issue 7 (15th December 2014) - Bevc, Staš; Junghans, Christoph; Praprotnik, Matej
<x xml:space="preserve">Abstract</x> We present a web toolkit STructure mapper and Online Coarse‐graining Kit for setting up coarse‐grained molecular simulations. The kit consists of two tools: structure mapping and Boltzmann inversion tools. The aim of the first tool is to define a molecular mapping from high, for example, all‐atom, to low, that is, coarse‐grained, resolution. Using a graphical user interface it generates input files, which are compatible with standard coarse‐graining packages, for example, Versatile Object‐oriented Toolkit for Coarse‐graining Applications and DL_CGMAP. Our second tool generates effective potentials for coarse‐grained simulations preserving the structural properties, for example, radial distribution functions, of the underlying higher resolution model. The required distribution functions can be provided by any simulation package. Simulations are performed on a local machine and only the distributions are uploaded to the server. The applicability of the toolkit is validated by mapping atomistic pentane and polyalanine molecules to a coarse‐grained representation. Effective potentials are derived for systems of TIP3P (transferable intermolecular potential 3 point) water molecules and salt solution. The presented coarse‐graining web toolkit is available at http://stock.cmm.ki.si. © 2014 Wiley Periodicals, Inc.